Vaginal and neonatal microbiota in pregnant women with preterm premature rupture of membranes and consecutive early onset neonatal sepsis - Luiz Gustavo dos Anjos Borges; Jana Pastuschek; Yvonne Heimann; Kristin Dawczynski; PEONS study group; Ekkehard Schleußner; Dietmar H. Pieper; Janine Zöllkau (BMC Medicine, 2023)
Abstract Background Preterm premature rupture of membranes (PPROM), which is associated with vaginal dysbiosis, is responsible for up to one-third of all preterm births. Consecutive ascending colonization, infection, and inflammation may lead to relevant neonatal morbidity including early-onset neonatal sepsis (EONS). The present study aims to assess the vaginal microbial composition of PPROM patients and its development under standard antibiotic therapy and to evaluate the usefulness of the vaginal microbiota for the prediction of EONS. It moreover aims to decipher neonatal microbiota at birth as possible mirror of the in utero microbiota. Methods As part of the PEONS prospective multicenter cohort study, 78 women with PPROM and their 89 neonates were recruited. Maternal vaginal and neonatal pharyngeal, rectal, umbilical cord blood, and meconium microbiota were analyzed by 16S rRNA gene sequencing. Significant differences between the sample groups were evaluated using permutational multivariate analysis of variance and differently distributed taxa by the Mann–Whitney test. Potential biomarkers for the prediction of EONS were analyzed using the MetaboAnalyst platform. Results Vaginal microbiota at admission after PPROM were dominated by Lactobacillus spp. Standard antibiotic treatment triggers significant changes in microbial community (relative depletion of Lactobacillus spp. and relative enrichment of Ureaplasma parvum) accompanied by an increase in bacterial diversity, evenness and richness. The neonatal microbiota showed a heterogeneous microbial composition where meconium samples were characterized by specific taxa enriched in this niche. The vaginal microbiota at birth was shown to have the potential to predict EONS with Escherichia/Shigella and Facklamia as risk taxa and Anaerococcus obesiensis and Campylobacter ureolyticus as protective taxa. EONS cases could also be predicted at a reasonable rate from neonatal meconium communities with the protective taxa Bifidobacterium longum, Agathobacter rectale, and S. epidermidis as features. Conclusions Vaginal and neonatal microbiota analysis by 16S rRNA gene sequencing after PPROM may form the basis of individualized risk assessment for consecutive EONS. Further studies on extended cohorts are necessary to evaluate how far this technique may in future close a diagnostic gap to optimize and personalize the clinical management of PPROM patients. Trial registration NCT03819192, ClinicalTrials.gov. Registered on January 28, 2019.